The next stage of devolution?: A (d)evolving criminal justice system for Wales? - Jones, Jackie (Crimes and misdemeanours, 2008)
The coalition government in Wales has committed itself to seriously consider devolving the criminal justice system for Wales. It is seen as the next possible step in the devolution process. To some extent many of the structures for a devolved criminal justice system are already being put in place to support devolved policy making and provision of criminal justice services in Wales. However, the One Wales agreement proposes to place the most emphasis on a devolved criminal justice system on youth justice and the prevention of reoffending. This is problematic in a number of ways explored in the paper, not least because the duties in the Welsh Constitution obligate the Welsh Assembly Government to ensure equality of opportunity for all and equality of treatment of both Welsh and English. Can a successful devolved fit-for-purpose criminal justice system for Wales be created?